Intervenções de enfermagem para o controle do diabetes : ensaio clínico randomizado - Capellari, Claudia (2018)
Introduction: Diabetes mellitus (DM) is a very common pathology, which can lead to chronic kidney disease (CKD) and the need for renal replacement therapy. In people with CKD and DM, glycemic control is critical for the prevention of microvascular lesions. In this context, the Nursing Process (NP) is the instrument to guide care, contributing to the attention of the needs of individuals. Objective: To evaluate the Nursing Interventions Classification (NIC) impact to diabetes control, in people with diabetes on hemodialysis diagnosed with NANDA-I diagnosis Risk for Unstable blood glucose level, trough the results of Nursing Outcomes Classification (NOC). Method: Randomized clinical trial in three dialysis services in southern Brazil. Population: Diabetic patients on hemodialysis. Sample: More than 18 years old, literate. Exclusion criteria: severe uncorrected deficiency in hearing, speech, total amaurosis, degenerative neurological diseases or scoring less than 20 in the Mini Mental State Examination. The sample consisted of 56 participants, 27 in the control group and 29 in the intervention group. Randomization occurred in groups, considering dialysis shifts. The control group followed the routine treatment and guidelines, while the intervention group received nursing interventions from the NIC for 6 months. The clinical variables related to the NOC results and the knowledge, attitude and self-care tests for DM were applied before and after the intervention period. After the interventions, a washout period of 06 months occurred, after which the variables were collected. Results: There were no differences between the groups in relation to the sociodemographic or clinical variables at the beginning of the study. The measurement of glycated hemoglobin in the intervention group was 7.7 ± 1.8; 7.0 ± 1.4 and 7.5 ± 2.1 mg / dl and 7.9 ± 2.2; 8.3 ± 2.3 and 8.4 ± 1.9 mg / dl in the control group at time zero, 6 and 12 months, respectively. There was significant improvement in knowledge, coping with diabetes and self-care, as well as in the NOC score Self-control of diabetes, Knowledge: diabetes control and glycemic level. Although the remaining knowledge and coping were observed after the washout period, the results point to a decrease in metabolic control. Conclusion: Nursing interventions based on NIC, applied to people with diabetes on hemodialysis, with a nursing diagnosis Unstable Glycemia, were effective for the knowledge, coping and self-care in relation to diabetes, positively impacting NOC nursing results Self-control of diabetes, knowledge : control of diabetes and glycemic level. Even with the best knowledge and self-control of diabetes, the results point to the need for continuous interventions with the group, the focus of this study, to achieve adequate long-term control of diabetes.